The adaptation of soldiers to post-service life – the mediating impact of political views on the relationship between violence and adaptation - Ben-Shalom, Uzi; Reizer, Abira; Connelly, Vincent; Rickover, Itamar (Frontiers in Psychology, 2023)
The current research explores the association between political views, combat experiences, and the adaptation of soldiers to post-service life. Violent experiences in military service were explored as contributors to both positive and negative dimensions of adaptation, while political views served as possible mediators. Three hundred and twenty Israeli veterans participated in the study. Political views were correlated with adaptation, especially left-to-right voting and anti-militarism. The results support the mediating role of political beliefs (left-right voting and militarism) in the relationship between combat experience and adaptation to post-service life. We contend that political perceptions affect adaptation through sense-making of the combat experiences and the individual processing of these experiences, and the willingness to continue in reserve service, which allows social support and recognition. In addition, they are linked to a sense of bitterness following the reduction of public participation in military and reserve service.